A Brand Ambassador for Purchasing Decision Mediheal Sheet Mask User's in Karawang - Imani, Afifah Nurul; Martini, Nelly (APTISI Transactions on Management (ATM), 2021)
Mediheal is a well-known sheet mask brand in South Korea. Bringing K-Pop idols together and also the widespread influence of Korean culture in Indonesian, have made skincare products famous in Indonesian. This study aims to determine, test, and analyze how much influence the brand ambassadors and Korean wave have on the purchasing decisions of Mediheal sheet mask users. The method used is descriptive and verification with a quantitative approach. Data were analyzed using path analysis and hypothesis testing using partial and simultaneous. With a sample of 100 respondents. The results showed that there was a relationship between brand ambassadors and the Korean waves of 33.4%. Partially, brand ambassadors and the Korean wave both have a significant effect on purchasing decisions. Brand ambassadors have an influence of 22.5% on purchase decisions, and Korean waves have an influence of 24.4% on purchasing decisions. Meanwhile, simultaneously, brand ambassadors and the Korean wave contributed 14.6% to purchasing decisions, then 85.4% of purchase decisions were influenced by other variables that were not studied.